DEVELOPMENT OF A RESTRICTION FRAGMENT LENGTH POLYMORPHISM METHOD FOR GENOTYPING THE ATP2B1 RS2681492 POLYMORPHISM IN VIETNAMESE POPULATION - Bùi, Thị Thúy Nga; Nguyễn, Thị Thanh Huyền; Nguyễn, Ánh Ngọc; Trần, Quang Bình (Tạp chí Dinh dưỡng và Thực phẩm, 2024)
Aims: The rs2681492, a single nucleotide polymorphism in the ATP2B1 gene, has been reported to be associated with cardiovascular diseases and traits including blood pressure, chronic heart failure, and hypertension. The study aimed to develop a PCR-RFLP genotyping method for rs2681492 among the Vietnamese population. Methods and Results: The Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method incorporated optimizations of primers, thermal cycles, and restriction enzymes in a novel restriction fragment length polymorphism (RFLP) approach. To evaluate the accuracy of the PCR-RFLP method, three different genotypes (AA, AG, and GG) were confirmed by gene sequencing. The experimental results determined the annealing temperature of 55°C for PCR and the minimum of 3 units of restriction enzyme HaeII for incubation with the PCR product. Conclusion: This optimal PCR-RFLP method was successfully applied to genotype ATP2B1 rs2681492 in large populations to investigate the association between the rs2681492 polymorphism and cardiovascular diseases.